Clinical Characteristics of Alcohol-Related Liver Disease in Albanian Patients: A Cross-Sectional Study - Dorina Osmanaj; Floreta Kurti; Klerida Shehu; Yllka Themeli; Gentian Stroni; Erand Llanaj; Adriana Babameto (Gastroenterology Insights, 2025)
Background/Objectives: Alcohol-related liver disease (ARLD) is a major cause of chronic liver disease, yet its clinical profile in Albania, a region with high HBV prevalence and rising alcohol consumption, remains poorly characterized. This study evaluates the clinical markers of advanced ARLD as noninvasive fibrosis indicators, acknowledging limitations in observational data and the need for validation in diverse populations. Methods: In this cross-sectional study, 200 patients with ARLD were classified as having mild or advanced disease based on clinical, biochemical, and imaging criteria. Associations between socioeconomic factors, nutritional status, and fibrosis markers with advanced ARLD were assessed using multivariate logistic regression, adjusted for age, sex, smoking status, and duration of alcohol use. Results: Lower Prognostic Nutritional Index (PNI) score was significantly associated with advanced ARLD (OR 0.95, 95% CI 0.91–0.99; p = 0.014), suggesting a potential role of nutritional status in disease progression. Higher APRI and FIB-4 scores were associated with an increased risk of advanced ARLD (APRI: OR 1.27, 95% CI 0.71–2.26; FIB-4: OR 1.10, 95% CI 0.81–1.51), though these associations did not reach statistical significance. Conclusions: This study provides a first clinical assessment of ARLD in Albania, highlighting the potential role of nutritional and fibrosis markers in risk stratification. While the study design limits definitive conclusions, our findings underscore the need for larger prospective studies to validate these associations and further investigate the influence of metabolic and socioeconomic factors on ARLD progression in Albania.